Implementasi Pembelajaran Berbasis Proyek Daur Ulang Sampah Terhadap Kesadaran Lingkungan dan Keterampilan Abad 21 Siswa Mi Tahfizh Al Falakiyah - Fauziah, Ratu Dinny; Risdiana (Equilibrium: Jurnal Pendidikan, 2025)
Environmental issues, particularly the increase in waste volume, have become a global problem that requires decisive action from all sectors of society. In education, the challenge lies in raising environmental awareness and equipping the younger generation with relevant knowledge for the 21st century from an early age. The objective of this study is to explain how the Project-Based Learning (PjBL) model is applied in non-organic waste recycling activities at MI Tahfizh Al Falakiyah and to examine how it impacts students' environmental awareness and skills in the modern era. To support the research findings, a qualitative-descriptive method supported by quantitative data was employed. Data was collected through observation, interviews, and student project assessments. Data validity was tested using source triangulation. The model used by Miles and Huberman for data analysis included presentation, reduction, and conclusion drawing. The research results showed that the implementation of PjBL in the waste recycling project was successfully carried out and helped students learn contextually. Students' environmental awareness increased as a result of this process. This was demonstrated by changes in their perceptions of waste and their understanding of the 3R principles (Reuse, Reduce, Recycle). Additionally, this approach effectively instilled modern skills, such as innovation in transforming waste into valuable items and collaboration in projects. Project assessment results showed that most student groups were able to create recycled items effectively; this indicates that the project was successful. Thus, the PjBL model with waste recycling activities is an effective and sustainable way to teach MI Tahfizh Al Falakiyah students important skills and environmental awareness.   Keywords : Learning Implementation, Waste Recycling, Environmental Awareness, 21st Century Skills.